Effectiveness of treatment measures for otodectosis, sarcoptosis and demodecosis in dogs - Melezhyk А.; Plakhotna, Ye.; Korchan, L.; Mykhailiutenko, S.; Zamaziy, A. (Scientific Progress & Innovations, 2025)
Among the acaroses caused by acariform mites, the most common in dogs in most countries of the world are otodectosis, demodicosis, and sarcoptosis, which are species-specific and persistent ectoparasites. There are a significant number of drugs on the veterinary market that, according to the instructions, have a detrimental effect on acariform mites. Moreover, their number increases every year due to the emergence of new, more modern drugs. At the same time, there is not always data on experimental testing of acaricidal drugs available on the market, which does not allow for complete information for effective selection of therapeutic drugs. Therefore, the aim of the research was to establish the effectiveness of modern drugs in the treatment of dogs suffering from otodectosis, sarcoptosis and demodicosis. Infested dogs were treated with: Simparica (AI – sarolaner; Zoetis Inc., USA), AcaroStop (AI – amitraz; ProVet, Ukraine) and AcaroSpectra (AI – imidacloprid, lufenuron, milbemycin oxime; SkyVet, Ukraine). The conducted studies showed that for otodectosis in dogs, the drugs Simparica, AcaroSpectra and AcaroStop provided 100 % effectiveness on the 20th day of treatment. However, the shortest recovery period was observed with the use of Simparica and AcaroSpectra, which was 10 days. For demodicosis in dogs, the most effective drugs that provided 100 % effectiveness were Simparica and AcaroSpectra. Moreover, the recovery period with the use of Simparica was 15 days, and with the use of AcaroSpectra – 20 days. When using the drug AсaroStop, the extent and intensity effectiveness were: on 5th day – 0 and 60.5 %, on 10 th day – 0 and 69.8 %, on 15 th day – 33.7 and 76.7 %, on 20 th day – 66.7 and 76.7 %, respectively. For sarcoptosis in dogs, all drugs provided 100 % effectiveness on day 20 of treatment. However, the shortest recovery period was observed when using the drugs Simparica and AсaroSpectra, which was 10 and 15 days, respectively. At the same time, when using the drug AcaroStop, the extent and intensity effectiveness were: on 5th day – 0 and 60.5 %, on 10 th day – 0 and 69.8 %, on 15 th day – 33.7 and 76.7 %, on 20 th day – 66.7 and 76.7 %, respectively. The results obtained will allow us to recommend the drugs Simparica and AcaroSpectra for the effective treatment of dogs with otodectosis, sarcoptosis and demodicosis.